PENERAPAN DIGITAL MARKETING SEBAGAI STRATEGI PEMASARAN UMKM PRODUK DIMSUM DI KOTA GIANYAR - Kadek Asmira Yanti; Dedy Darmawan (Paser Institute Management and Busines, 2026)
This research is motivated by the development of digital technology that encourages MSME actors to adapt their marketing strategies in order to compete in the digital era. Dimsum MSMEs in Gianyar City face challenges in conventional marketing, making the implementation of digital marketing. The purpose of this study is to analyze the implementation of digital marketing as a marketing strategy for dimsum MSMEs in Gianyar City. The research method uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation involving business owners, marketing employees, and consumers. The results of the study indicate that digital marketing through social media, online delivery platforms, and digital content is able to increase market reach, sales, and interaction with consumers. The quality of digital content also influences consumer buying interest. The conclusion that digital marketing is effective in improving the marketing performance of dimsum MSMEs in Gianyar City, although there are still obstacles related to technological capabilities and content consistency. This study is the need to improve the digital literacy of MSME actors, provide training in content management, and optimize the sustainable use of digital platforms so that marketing can be maximized.